Impact of coagulopathy in geriatric traumatic brain injury - Jadhao, Suraj; Bairwa, B. L.; Sharma, Vinod; Chopra, Sanjeev (International Journal of Research in Medical Sciences, 2022)
Background: Traumatic brain injury (TBI) is the leading cause of death in trauma patients in various parts of the world including India. Coagulation cascade is affected in TBI. The severity of coagulopathy correlates with degree of primary injuries thus affecting the prognosis of geriatric patients. Since the prognosis of isolated TBI can be a challenge to predict at times. AIM: we wanted to study the potential of international normalized ratio (INR) test, prothrombin test (PT), platelet count as a prognostic tool in isolated TBI. Methods: INR, PT, platelet count reflects the coagulation status. In most trauma cases, it is a routine test as well. We collected the INR, PT, platelet count value at admission of 200 isolated geriatric TBI cases over a period of three months. Then, patients were followed-up and their outcome at three months from admission is scored using Glasgow outcome scale (GOS). The relationship of INR, PT, platelet count with GOS was studied. Results: From our limited study, we found that INR of 1.52, PT 17 sec or more and platelet count less than 1.10 lac predicts poor prognosis in cases of isolated geriatric TBI. Conclusions: It is important to early diagnose and early manage the coagulation abnormalities in isolated geriatric head injury patients.